Systemic lupus erythematosus presenting with cardiac tamponade. Issue 4 (April 1984) - Carroll, N; Barrett, J A
Abstract : A previously well 36 year old man presented with cardiac tamponade as the initial manifestation of systemic lupus erythematosus. This diagnosis should, therefore, be considered not only in cases of pericarditis but also in those of tamponade.